Предмет: Математика,
автор: Zemacom
помогите пожалуйста решить это задание
Приложения:
![](https://files.topotvet.com/i/5bf/5bf67b9729a0029fa6d3fb8813d2fc59.jpg)
Ответы
Автор ответа:
1
(3x3+cos(2x))' = (3x3)' + (cos(2x))' = (9x2) + (-2sin(2x)) = 9x2-2sin(2x)
Производную этого выражения находим по формуле: (xn)' = n*xn-1
(3x3)' = 3*3x3-1(x)' = 9x2
(x)' = 1
Здесь:
(cos(2x))' = (cos(2x))'(2x)' = -2sin(2x)
(2x)' = 2
Ответ:
9x2-2sin(2x)
Производную этого выражения находим по формуле: (xn)' = n*xn-1
(3x3)' = 3*3x3-1(x)' = 9x2
(x)' = 1
Здесь:
(cos(2x))' = (cos(2x))'(2x)' = -2sin(2x)
(2x)' = 2
Ответ:
9x2-2sin(2x)
Похожие вопросы
Предмет: Химия,
автор: gruniyovaliuba
Предмет: Геометрия,
автор: belosohova07
Предмет: Окружающий мир,
автор: danafursov4
Предмет: Математика,
автор: кет49
Предмет: Математика,
автор: Тамер12345678